Executive summary [in Boosting growth to end hunger by 2025: The role of social protection] - Wouterse, Fleur Stephanie; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
The 2017-2018 Annual Trends and Outlook Report (ATOR) takes an in-depth look at social protection in rural Africa to address these three questions, which are particularly relevant as Africa embarks on the implementation of the Malabo Declaration commitments and the African Union’s Agenda 2063. First, the contributed chapters summarize and synthesize the available evidence on successful implementation of social protection programs in rural Africa. Second, the report fills in knowledge gaps on how to maximize the role of social protection in reducing vulnerability and increasing resilience of rural households. Third, the report highlights policy implications to guide the design and roll-out of national social protection programs for rural Africa.